An analysis of diurnal cycles in the mass of ambient aerosols derived from biomass burning and agro‐industry. Issue 15 (6th August 2013) - Caetano‐Silva, L.; Allen, A. G.; Lima‐Souza, M.; Cardoso, A. A.; Campos, M. L. A. M.; Nogueira, R. F. P.
Abstract: [1] Strong diurnal cycles in ambient aerosol mass were observed in a rural region of Southeast Brazil where the trace composition of the lower troposphere is governed mainly by emissions from agro‐industry. An optical particle counter was used to record size‐segregated aerosol number concentrations between 13 May 2010 and 15 March 2011. The data were collected every 10 min and used to calculate aerosol mass concentrations. Aerosol samples were also collected onto filters during daytime (10:00–16:00 local time) and nighttime (20:00–06:00) periods, for subsequent analysis of soluble ions and water‐soluble organic carbon. Biomass burning aerosols predominated during the dry winter, while secondary aerosols were most important in the summer rainy season. In both seasons, diurnal cycles in calculated aerosol mass concentrations were due to the uptake of water by the aerosols and, to a lesser extent, to emissions and secondary aerosol formation. In neither season could the observed mass changes be explained by changes in the depth of the boundary layer. In the summer, nighttime increases in aerosol mass ranged from 2.7‐fold to 81‐fold, depending on particle size, while in the winter, the range was narrower, from 2.2‐fold to 9.5‐fold, supporting the possibility that the presence of particles derived from biomass burning reduced the overall ability of the aerosols to absorb water. Key Points: Diurnal cycle of agro‐industrial aerosol mass governed by humidity Biomass burning emissions act to suppress particle growth Need to consider diurnal mass cycles in aerosol dry deposition models